Telling friend from foe: environmental cues improve detection accuracy of individuals with hostile intentions - Wijngaarden, R. J. van (Legal and criminological psychology, 2017)
Purpose. Detecting deviant behaviours that precede and are related to crimes can help prevent these crimes. Research suggests that the psychological mindset of wrongdoers may differ from others, such that they are more anxious, self-focussed, and vigilant. As a result, their responses to environmental cues, specifically those that signal risk of exposure, may differ. Method. In two randomized controlled trials, participants with high (vs. low) cognitive load walked a pre-defined route to carry out a hostile or non-hostile task. En route, participants were exposed to a strong (vs. mild) cue from a security officer (Study 1), or a cue (vs. no cue) resembling police walkie-talkie static noise (Study 2). Participants filled out a questionnaire measuring psychological constructs. Reactions during the task were recorded and presented to independent observers to determine the participants’ intent. Results. Participants with high (vs. low) cognitive load who were exposed to a strong (vs. mild or no) cue while carrying out their task were more often correctly identified by observers as either innocent or hostile based on their behaviour. Analysis of the questionnaire revealed that the experience of hostile intentions is related to anxiety, inhibitory control of anxiety, activation control of normal behaviour, and to other relevant constructs which may explain why cues that signal risk of exposure can improve the detection accuracy of individuals with hostile intentions. Conclusion. These studies show that cues that signal risk of exposure can improve the detection of wrongdoers and the role of self-regulation in the suppression of anxiety and deviant behaviours.